Effectiveness of Instructional Program upon Pregnant Women’s Knowledge Suffering from Pregnancy Induced Hypertension Attending to Primary Health Care Centers in Al- Najaf City - Anwar Hassan Hanoon; Shukriyia Shadhan Al- Ogaili (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pregnancy induced hypertension is a common obstetric disorder. It is among the leading causes of maternaland fetal mortality and morbidity. This research aims to assess pregnant women’s knowledge regardingpregnancy induced hypertension, and to find out the relationship between pregnant women’s knowledge andtheir demographic and clinical data . A quasi-experimental design is used to investigate the effectivenessof instructional program upon women’s knowledge suffering from pregnancy induced hypertension , fromthe 8th of January to 3th September2020, included 80 pregnant (40 women as study group), and (40 womenas a control group). The current study found that the knowledge of the majority of women about pregnancyinduced hypertension is poor in complication domain specialty before the implementation of instructionalprogram. However, 100% of them have had good knowledge after two weeks of implementation of theinstructional program. The women have developed and improved in their knowledge about pregnancyinduced hypertension. The study revealed that there were high significant in the study group knowledgeregarding the pregnancy induced hypertension in the pre-test and post-test measurements. The study hasconcluded that the instructional program has a positive effect on the study sample blood pressure. Theinstructional program has a positive effect on the study sample knowledge regarding the PIH. Levels ofeducation, monthly income, residential area, occupational status, and the type of family are affect thepregnant’s knowledge regarding the PIH.